Patients' and surgeons' experiences after failed breast reconstruction: A qualitative study. Issue 7 (July 2021) - Kouwenberg, Casimir A.E.; van Hoogdalem, Lothar E.; Mureau, Marc A.M.; Ismail, Sohal; Gopie, Jessica P.; Tibben, Aad; Kranenburg, Leonieke W.
Summary: Background: The goal of postmastectomy breast reconstruction (BR) is to improve the quality of life of patients. However, complications following autologous BR (A-BR) and implant-based BR (I-BR) occur frequently and may even lead to BR-failure, which can be a distressing event for both patients and surgeons. The current study, therefore, examines the experiences of both patients and surgeons after a BR-failure. Methods: Patients with a failed BR from a large multicenter cohort study and participating plastic surgeons were invited to participate in semi-structured interviews focusing on their experiences. The interviews were analyzed according to the principles of grounded theory. Results: Fourteen patients with a failed I-BR, four patients with a failed A-BR, and four plastic surgeons were participated. Three main categories emerged from the data: personal experiences with BR-failure, the motives for a redo of a failed BR, and patient–surgeon communication. Patients would like to be treated with more attention to their personal feelings and lives, instead of being approached from a purely medical-technical perspective. Surgeons may experience feelings of guilt leading to the strong urge to fix the failed BR, whereas patients may be less inclined to undergo additional operations. Patients want to know what the choice for a particular type of BR would mean to their personal lives. The impact of I-BR-failure may be underestimated and requires the same degree of intensive aftercare and attention. Conclusions: Implementing the recommendations of this study in clinical practice may facilitate improvements in how both patients and surgeons cope with a BR-failure.